THE EFFECT OF USING DIFFERENT UFLPLUS (UNDERWATER FISH LAMP PLUS) LIGHT COLORS ON THE ABUNDANCE OF PLANKTON IN THE WATERS OF WAWONII ISLAND - Fajriah, Fajriah; Isamu, Kobajashi Togo (Jurnal Penelitian Perikanan Indonesia, 2024)
Plankton are small organisms that have an important role in the survival of many organisms in the waters. The abundance of plankton, especially phytoplankton, depends on the presence of light. This study aim to determine the effect of different colors of UFLPlus light (yellow and green) to the abundance and biological index of plankton in the Waters of Wawonii Island. The research was conducted using a purposive sampling method which consisted of 4 trips. Sampling was carried out using a plankton net for 3 repetitions in each trip. The obtained data of light color differences were determined using the abundance formula and biological index. All data was analyzed using the Mann Whitney Non-Parametric test. The results showed that the genus Oscillatoria sp and Chaetoceros sp were the most common genera found in all trips. The average abundance of plankton in the waters of Wawonii Island, Konawe Islands using green UFLPlus light was 4699 Ind/L, higher than the average abundance of plankton using yellow UFLPlus light of 3115 Ind/L. The plankton diversity index showed low category (1,2), while the evenness index is low category (0,4) and there is no dominance (0,23) (p=0,2). The different colors of UFLPlus light (yellow and green) did not give a significant impact on the abundance and biological index of plankton (low category for diversity and uniformity index, while has no dominance species), especially for Oscillatoria sp and Chaetoceros sp in the Waters of Wawonii Island.